Контроль качества обработки и состояния режущего инструмента по звуку, сопровождающему процесс резания - Залога, Вильям Александрович; Нагорный, В. В. (НТУ "ХПИ", 2014)
Эффективность диагностики и оптимизация процесса резания целиком и полностью определяется информативностью контролируемых параметров. На практике приходится существенно ограничивать объем диагностической информации. Поэтому существует задача выбора контролируемого параметра, позволяющего в условиях промышленного производства эффективно оценивать качество металлообработки. Выбору подобного параметра – звукового сигнала, сопровождающего процесс резания, и посвящена данная статья. В результате расчетно-экспериментальных исследований установлено, что частотные и временные параметры звука, возникающего при резании, тесно коррелированы с шероховатостью обработанной поверхности и с изменением геометрических параметров лезвия инструмента.

Diagnostic efficiency and optimization of the cutting process entirely determined informative controlled parameters. Naturally, the more subject to the control parameters, the more precisely controlled state of the technological system of metal.However, in practice it is essential to limit the amount of diagnostic information. The fact that the actual process system unlike laboratory research facility does not permit a plurality of sensors to produce the desired amount of the original information. Therefore, there is the problem select the parameter that allows an industrial production to effectively assess the quality of metalworking.Choice of this parameter-beep accompanying the cutting process, the focus of this article. The article shows that the frequency and timing of sound produced when cutting is closely correlated with the roughness of the treated surface. The availability of this correlation allows simultaneous control in the mode of present time is not only the quality of workpiece (surface finish), but also the condition of the cutting tool, as roughness is a "mirror image" state of the cutting blade tool, responsive to changes in the process of cutting its geometry, as well as to changes in the dynamic state of practically all other elements of the technological system.
Keywords: обработка материала; резание; режущий инструмент; автоматический контроль; металлообработка